Purun Bag Decoration Training for Women of Dharma Wanita Members as Part of Work-Life Balance - Swandari, Fifi; Said, Laila Refiana; Fariany, Gusti Rina; Ariffin, Zakhyadi; Claudia, Meiske; Prihatiningrum, RR. Yulianti; Rusniati, Rusniati; Fatimah, Siti; Rizkya, Syafa (Universitas Lambung Mangkurat, 2025)
Dharma Wanita members who work on campus from Monday to Friday experience boredom. Prolonged boredom will lead to stress at work. Constant stress can negatively impact mental or physical health. Another problem faced by Dharma Wanita members is a lack of income. The aim of this community service activity is twofold. First, teach a new hobby to reduce stress levels at work. Second, it gives participants the possibility to earn additional income. The implementation method used is training and mentoring. There are two main activities of PDWA. The first is training to decorate basic-level purun bags, and the second activity is training to decorate advanced-level purun bags. The first activity, Purun Bag Decoration Training for Women Members of Dharma Wanita, was held on Friday, August 23, 2024. This activity took place at the Sari Patin Depot, Jl. Brigadier General H. Hasan Basry Kayu Tangi. This activity went smoothly. The second stage of activity, namely Advanced Level training, will be held on October 18, 2024. The results of this activity are two. Participants feel relaxed and ultimately reduce stress at work. The second result is still potential because the process of a hobby becoming income takes a long time. From this activity, it can be concluded that most participants are able to decorate as they have been taught, but to become a source of income, they still need a lot of practice.